How Are Derivatives Used? Evidence From the Mutual Fund Industry - Koski, Jennifer Lynch; Pontiff, Jeffrey (Journal of Finance, 1999)
We investigate investment managers' use of derivatives by comparing return distributions for equity mutual funds that use and do not use derivatives. In contrast to public perception, derivative users have risk exposure and return performance that are similar to nonusers. We also analyze changes in fund risk in response to prior fund performance. Changes in risk are substantially less severe for funds using derivatives, consistent with the explanation that managers use derivatives to reduce the impact of performance on risk. We provide new evidence regarding the implications of cash flows and managerial gaming for the relation between performance and risk.